The interrater reliability of Modic changes among a potential basivertebral nerve ablation population: Why AC1 may be preferred to kappa. Issue 5 (18th October 2022) - Sherwood, David; Haring, Richard Sterling; Schirmer, Derek; Modic, Michael
Abstract: Interrater reliability of Modic changes is subject to variables which affect consistency in reporting. Given the importance of Modic change identification for basivertebral nerve ablation (BVNA) candidacy, interrater reliability for this specific cohort has not yet been reported. Twenty lumbar magnetic resonance images of potential basivertebral nerve candidates were independently reviewed by two neuroradiologists and two interventional spine physiatrists for the presence and characterization of Modic changes. The kappa value of their agreement on the presence of Modic changes was 0.52 (95% confidence interval [CI] 0.37–0.67), whereas agreement on the type of Modic change was 0.51 (95% CI 0.37–0.65). Using an alternative methodology for measuring interrater reliability (Gwet's AC1) yielded the identification of the presence of Modic changes at AC1 0.51 (95% CI 0.36–0.66), whereas agreement on the type of Modic change was AC1 0.75 (95% CI 0.66–0.83). While less common, AC1 may be preferred in the appropriate cohort to kappa as it mitigates some of the pitfalls to which kappa values may be victim. Ultimately, our results are in‐line with previous reports of interrater reliability results for Modic changes in other cohorts and should serve to caution those who perform BVNA regarding interrater agreement of the imaging crux of the procedure.